The prevalence of mandibular retromolar canals on cone beam computed tomography and its clinical repercussions - George Borja de FREITAS; Alessandra de FREITAS E SILVA; Luiz Roberto Coutinho MANHÃES JÚNIOR (Universidade Estadual Paulista, 2017)
Abstract Introduction Knowledge on the normal morphology of the human mandible and its possible anatomical variations are of fundamental importance in dental practice, especially in the areas of surgery and implantodontics. The retromolar region is delimited by the anterior margin of the ramus of the mandible, the temporal crest and the distal surface of the last lower molar. In this area, a retromolar canal may be observed emerging through the retromolar foramen. Objective This study aims to evaluate the prevalence of retromolar canals in cone beam computed tomography (CBCT) images and to correlate it with their possible clinical repercussions. Material and method 300 CBCT images were selected from the Department of Radiology of the São Leopoldo Mandic Dental School. This was an observational descriptive study and all the images were processed and analyzed on XoranCat®. Result Of the 300 CFCT scans analyzed, a single mandibular canal was observed in 210 (70.0%). In the remaining 90 cases, anatomical changes were observed relating to this canal, indicating that the prevalence of this condition in this sample was 30%. The prevalence of retromolar canals was observed in 15 patients (5.0%), of which 06 were in males and 09 in females. Conclusion The importance of a full knowledge on the anatomy of the retromolar region is herein reiterated due to the high prevalence of surgical procedures in the posterior region of the mandible, which could optimize predictability at treatment planning as well as anesthetic and surgical outcomes, thus minimizing anesthetic failures and surgical accidents.